Answer:
9/16
Step-by-step explanation:
![f(x)=-\frac{9}{x}](https://tex.z-dn.net/?f=f%28x%29%3D-%5Cfrac%7B9%7D%7Bx%7D)
![f(x)=-9x^{-1}](https://tex.z-dn.net/?f=f%28x%29%3D-9x%5E%7B-1%7D)
Derivative rule:
![f(x)=x^{n} \\](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E%7Bn%7D%20%5C%5C)
![\frac{df}{dx}=nx^{n-1}](https://tex.z-dn.net/?f=%5Cfrac%7Bdf%7D%7Bdx%7D%3Dnx%5E%7Bn-1%7D)
Here, n=-1, so
![\frac{df}{dx}=(-9)(-1)x^{-2} =\frac{9}{x^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7Bdf%7D%7Bdx%7D%3D%28-9%29%28-1%29x%5E%7B-2%7D%20%3D%5Cfrac%7B9%7D%7Bx%5E%7B2%7D%20%7D)
Evaluating this at x=-4 gives 9/16
Answer:
is a trinomial having three terms, with degree 5 and the constant term '3'.
Step-by-step explanation:
Considering the trinomial
![4x^5\:+\:9x^2\:+\:3](https://tex.z-dn.net/?f=4x%5E5%5C%3A%2B%5C%3A9x%5E2%5C%3A%2B%5C%3A3)
As the polynomial contains 3 terms, so it is a trinomial.
As the highest power of the variable 'x' is 5, so the degree of this polynomial is 5.
Any term with no variable is called a constant term. so, 3 is a term with no variable. Therefore, the constant term is 3.
Therefore,
is a trinomial having three terms, with degree 5 and the constant term '3'.
The length of both rooms is 10 meters and the width for the kitchen is 5 meters, while the one for the dining room is 9 meters.
<h3>How to find the length of the rooms?</h3>
Both rooms have the same length but different areas and different widths. This common measurement can be found using the GFC or the greatest common factor. To do this, divide each number by 1,2,3, etc., and find the greatest common number (only integers are valid).
- 50: 50 25 10 5 1
- 90: 90 45 30 18 15 10 9 6 5 3 2 1
The greatest common number is 10, so 10 meters is the length of the room.
<h3>How to find the width?</h3>
Use the formula
- A = lenght x width or width = area / lenght
Kitchen.
- Width: 50 / 10
- Width: 5 meters
Dining room:
- Width: 90 / 10
- Width: 9 meters
Note: In this question the diagram is missing; below, I attach the diagram.
Learn more about greatest common factor in: brainly.com/question/282609
Answer:
See below
Step-by-step explanation:
To solve for d, multiply both sides of the equal sign by 4.
4(1/4d) = 4 (1/5g(g+e)-h)
4/4d = 4(1/5
+ 1/5ge - h)
d = 4/5
+ 4/5ge - 4h
-19 is the answer ////////////////// sorry i needed more charecters to answer